Efficacy and safety of benzalkonium chloride-free fixed-dose combination of latanoprost and timolol in patients with open-angle glaucoma or ocular hypertension - Bhagat P (Dove Medical Press, 2014)
Purvi Bhagat,1 Kalyani Sodimalla,2 Chandrima Paul,3 Surinder S Pandav,4 Ganesh V Raman,5 Rengappa Ramakrishnan,6 Abhijeet Joshi,7 Atul Raut7 1Glaucoma Clinic, M & J Western Regional Institute of Ophthalmology, Civil Hospital, Ahmedabad, Gujarat, India; 2Glaucoma Department, PBMA’s H.V. Desai Eye Hospital, Maharashtra, India; 3Glaucoma Service, B B Eye Foundation, Kolkata, India; 4Advanced Eye Centre, Postgraduate Institute of Medical Education and Research, Chandigarh, India; 5Glaucoma Clinic, Aravind Eye Hospital, Coimbatore, Tamilnadu, India; 6Glaucoma Clinic, Aravind Eye Hospital, Tirunelveli, Tamilnadu, India; 7Clinical Research Department, Sun Pharma Advanced Research Company Ltd, Mumbai, Maharashtra, India Background: Benzalkonium chloride (BAK) is a common preservative in topical ocular preparations; however, prolonged use may lead to deleterious effects on the ocular surface, affecting quality of life and reducing adherence to treatment and overall outcomes. This study compared the intraocular pressure (IOP)-lowering efficacy and safety of a novel once-daily, BAK-free, fixed-dose combination of latanoprost plus timolol with latanoprost or timolol administered as monotherapy or concomitantly. Methods: This was a 6-week, randomized, open-label, parallel-group, active-controlled study in patients aged ≥18 years with open-angle glaucoma or ocular hypertension. A total of 227 patients were randomized to either a once-daily, BAK-free, fixed-dose combination of latanoprost 0.005%/timolol 0.5% ophthalmic solution or concomitant administration of once-daily latanoprost 0.005% plus twice-daily timolol 0.5% or once-daily latanoprost 0.005% monotherapy, or twice-daily timolol 0.5% monotherapy. Efficacy end points were assessed at three time points on visits at weeks 1, 2, 4, and 6 versus baseline. Results: The IOP-lowering efficacy of the fixed-dose combination of latanoprost/timolol was similar to that of latanoprost plus timolol administered concomitantly at all time points (mean IOP difference and 95% confidence interval within ±1.5 mmHg; P=0.4223 to P=0.9981). The fixed-dose combination of latanoprost/timolol demonstrated significantly better IOP-lowering efficacy than timolol monotherapy at all time points (P=0.001 to P<0.0001) and significantly better IOP-lowering efficacy than latanoprost monotherapy at all time points. Responder rates on at least one time point and on at least two time points with fixed-dose combination latanoprost/timolol were similar to those with concomitant latanoprost plus timolol (85.5% versus 82.1%, P=0.6360; 78.2% versus 75%, P=0.6923), but significantly better than either latanoprost or timolol monotherapy (68.5%, P=0.0355; 55.4%, P=0.0005; 57.4%, P=0.0202; and 46.4%, P=0.0006, respectively). No significant differences in ocular and nonocular treatment-emergent adverse events were found between the treatment groups. Conclusion: A BAK-free, fixed-dose combination of latanoprost 0.005%/timolol 0.5% was as effective and well tolerated as concomitant latanoprost and timolol for treatment of elevated IOP in patients with open-angle glaucoma or ocular hypertension. Keywords: open-angle glaucoma, ocular hypertension, pharmaceutical preservatives, benzalkonium chloride, latanoprost, timolol